2019
DOI: 10.1101/2019.12.15.858340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FK506-binding protein 13 expression is upregulated in interstitial lung disease and correlated with clinical severity: a potentially protective role

Abstract: 23Pulmonary fibrosis is a progressive lung disease characterized by myofibroblast accumulation and 24 excessive extracellular matrix deposition. Endoplasmic reticulum (ER) stress initiates the unfolded 25 protein response (UPR), a cellular stress response pathway that has been implicated in both 26 inflammatory and fibrotic processes. Here, we sought to investigate the role of the 13 kDa FK506-27 binding protein (FKBP13), an ER stress-inducible molecular chaperone, in various forms of pulmonary 28 fibrosis. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Work completed using human lung tissues was as previously described. 60 In short, procedures using human tissues were approved by the Hamilton Integrated Research Ethics Board (11-3559 and 13-523-C). FFPE IPF lung tissue samples were acquired from the biobank for lung diseases at St. Joseph's Hospital in Hamilton, Ontario, and selected based on the evaluation of trained molecular pathologists and radiologists.…”
Section: Evidence Of Mmt In Vitromentioning
confidence: 99%
“…Work completed using human lung tissues was as previously described. 60 In short, procedures using human tissues were approved by the Hamilton Integrated Research Ethics Board (11-3559 and 13-523-C). FFPE IPF lung tissue samples were acquired from the biobank for lung diseases at St. Joseph's Hospital in Hamilton, Ontario, and selected based on the evaluation of trained molecular pathologists and radiologists.…”
Section: Evidence Of Mmt In Vitromentioning
confidence: 99%
“…FKPB13 is an endoplasmic reticulum (ER) chaperone (Tat et al 2021); the FKBP2 gene encodes FKBP13 (Boon et al 2009); its molecular function includes transport between trans-proline and cis-proline residues for appropriate folding of the protein in the lumen of the ER (Jeong et al 2017). FKBP13 has been reported to be upregulated through ER stress (Bush et al 1995) which is believed to be vital for the maintenance of ER protein homeostasis as part of the unfolded protein response (Jeong et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Do all ER chaperones play roles in lung fibrosis and interstitial lung disease, as does GRP78? Here, Tat and colleagues provide some mechanistic insight into another ER chaperone in lung fibrosis, the 13-kD FK506-binding protein (FKBP13) (7). Previous studies have reported finding increased expression of the FKBP2 gene (which encodes FKBP13) in fibrotic lungs and a correlation of expression levels with disease progression of lung fibrosis (8) and chronic hypersensitivity pneumonitis (9).…”
mentioning
confidence: 99%